1993
DOI: 10.1152/jn.1993.70.6.2251
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal inhibitory interneurons are functionally disconnected from excitatory inputs by anoxia

Abstract: 1. The effects of anoxia on inhibitory synaptic transmission were studied in hippocampal slices of 3- to 4-wk-old rats. CA1 pyramidal cells were examined by whole-cell patch-clamp recording. Synaptic currents were evoked by "distant" (> 0.5 mm) or "close" (< 0.5 mm) electrical stimulation in the stratum radiatum. 2. The excitatory postsynaptic currents (EPSCs) and inhibitory postsynaptic currents (IPSCs) evoked by distant stimulation were completely suppressed by brief anoxia (95% N2-5% CO2 for 4-6 min) and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
28
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(31 citation statements)
references
References 29 publications
3
28
0
Order By: Relevance
“…It is unlikely that the decrease in MEQ fluorescence was already maximal after OGD, thereby preventing any additional decrease in MEQ fluorescence by muscimol; other compounds such as NMDA produce even greater decreases in MEQ fluorescence than reported here (Inglefield and SchwartzBloom, 1998b). Other investigators have reported that GABA Amediated inhibition is suppressed immediately after anoxia in the hippocampal slice, because of a loss of excitatory input onto GABA-ergic interneurons (Krnjević et al, 1991;Khazipov et al, 1993). In contrast, Katchman et al (1994) proposed that the loss of GABA A -mediated inhibition immediately after anoxia was attributable to a decrease in extracellular Cl Ϫ .…”
Section: Ogd Effects On Intracellular CL ؊ and Synaptic Transmissionmentioning
confidence: 98%
“…It is unlikely that the decrease in MEQ fluorescence was already maximal after OGD, thereby preventing any additional decrease in MEQ fluorescence by muscimol; other compounds such as NMDA produce even greater decreases in MEQ fluorescence than reported here (Inglefield and SchwartzBloom, 1998b). Other investigators have reported that GABA Amediated inhibition is suppressed immediately after anoxia in the hippocampal slice, because of a loss of excitatory input onto GABA-ergic interneurons (Krnjević et al, 1991;Khazipov et al, 1993). In contrast, Katchman et al (1994) proposed that the loss of GABA A -mediated inhibition immediately after anoxia was attributable to a decrease in extracellular Cl Ϫ .…”
Section: Ogd Effects On Intracellular CL ؊ and Synaptic Transmissionmentioning
confidence: 98%
“…109,46 The inhibition is caused by failure of the excitatory input to inhibitory interneurons, leading to silencing of inhibitory interneurons. 110 This may contribute to excitotoxicity with delayed cell death. Also, it may lead to abnormal excitatory synchronicity after cerebral ischemia, manifesting as electroencephalographic status epilepticus in posthypoxic encephalopathy after cardiac arrest.…”
Section: Evidence Of Postsynaptic Failurementioning
confidence: 99%
“…In brain slice preparations, the evoked inhibitory postsynaptic current (IPSC; possibly polysynaptic) was suppressed under ischaemic conditions and was more sensitive to hypoxic insults than the evoked excitatory postsynaptic current (EPSC; Rosen & Morris, 1993). Recent findings suggest that the polysynaptic IPSC was sensitive to anoxia because excitatory input to the inhibitory interneurones are sensitive to it, while the monosynaptic IPSC is robust (Khazipov, Bregestovski & Ben-Ari, 1993). The monosynaptic GABAA receptor-mediated IPSC in CAl pyramidal neurones of the 3-to 4-week-old rat hippocampal slice was insensitive to anoxia, whereas the monosynaptic GABAB receptor-mediated IPSC was highly sensitive to the postsynaptic mechanism (Khazipov et al 1993).…”
mentioning
confidence: 99%
“…Recent findings suggest that the polysynaptic IPSC was sensitive to anoxia because excitatory input to the inhibitory interneurones are sensitive to it, while the monosynaptic IPSC is robust (Khazipov, Bregestovski & Ben-Ari, 1993). The monosynaptic GABAA receptor-mediated IPSC in CAl pyramidal neurones of the 3-to 4-week-old rat hippocampal slice was insensitive to anoxia, whereas the monosynaptic GABAB receptor-mediated IPSC was highly sensitive to the postsynaptic mechanism (Khazipov et al 1993). However, intracellular recording from CAl pyramidal neurones of the adult rat hippocampal slice showed a suppression (38-2 %) of monosynaptic GABAA-mediated IPSC, possibly by way of some postsynaptic effects (Zhu & Krnjevic, 1994).…”
mentioning
confidence: 99%